Urban foresters’ perceptions about the role of soil and fungi in urban forest management and climate mitigation - Nicola Radatus-Smith; Shashi Kant (The Forestry Chronicle, 2024)
The benefits of soil and mycorrhizal fungi in mitigating climate impacts through their vital role in carbon sequestration are well recognised in the academic literature but are not well incorporated in current urban forest planning and policies. We conducted a survey to examine urban foresters’ perceptions about the incorporation of current scientific understanding of the role of soil and fungi, and stakeholders’ engagement in urban forest management. Overall, urban foresters perceive that soil and fungi are important, however, little consideration is given to their incorporation in urban forest management practices and policies. Many stakeholders’ engagement is low in urban forest management. Urban foresters perceive that decision makers have little knowledge about the role of soil and fungi which may pose barriers to its integration in planning and policies. The key challenges revealed by the survey include the lack of funding, conflicting priorities, and the lack of mechanisms to transfer scientific knowledge to urban foresters and inter-departmentally. Municipalities should develop policies that enhance knowledge transfer and integration to enhance the efficacy of urban forest’s strategies that work to support municipal climate goals. Furthermore, collaboration with diverse stakeholder groups may enhance communication and subsequently increase support for urban forest initiatives.